A new species of Tyloperla (Plecoptera: Perlidae) from Guangxi, China, with a redescription of the male of T. sinensis Yang & Yang, 1993 - Mo, Raorao; Wang, Guoquan; Li, Weihai (Zootaxa, 2020)
One new species of the genus Tyloperla Sivec & Stark, 1988, T. bilobata sp. nov., is described from Guangxi Zhuang Autonomous Region of southern China. The new species is compared with related taxon. A redescription of the adult male of T. sinensis Yang & Yang, 1993 is also presented.